The use of statistical methods by MBA graduates in South African management and its implications for curriculum design - Trevor Wegner; Stephanie Stray; Peter Naudé (South African Journal of Business Management, 1994)
With this study we aim to identify the degree of penetration of statistical methods in South African management. Consequently, that section of the management population with past exposure to quantitative methods is targetted. Thus the target population was all MBA alumni from South African Business Schools operating in South African companies. A response rate of 27% (408 usable responses) was achieved. The findings of this study correlate highly with those of a similar survey conducted in the United Kingdom in 1991. In addition to reporting these findings, we also sought to examine the implications of these results on future statistical methods course planning. We recommend a change in teaching strategy to promote greater utilization of this discipline in practice.
Keywords: 650